Antimicrobial activity of citrus fruits and effects of key lime (Citrus aurantifolia christm. & panzer) juice extract on quality changes of white shrimp (Penaeus vannamei boone) - Velu, Selvi (2014)
The demand for novel antimicrobial agents and natural preservatives from natural resources has increased worldwide particularly in the food preservation field. In this study, antimicrobial activity of musk lime (Citrus microcarpa), key lime (Citrus aurantiifolia Christm. & Panzer) and lemon (Citrus limon) extracts were evaluated against various food borne pathogens and spoilage bacteria using the disc diffusion test. The antimicrobial activity was evaluated at 50% and 100% concentration level using various extraction solvents’ ethanol (food grade), water and juice. Alternatively, no information was available regarding application of key lime (KL) juice extract as a preservation agent for white shrimp (Penaeus vannamei Boone). Hence, this study further aimed to investigate the effect of the key lime juice extract (100% concentration level) in combination with vacuum packaging (VP) and storage bag (SB) on microflora and biochemical changes in white shrimp stored at 2±1 ºC. Microbiological and biochemical analysis were carried out at 3 days interval till the 12th day of storage. Microbiological analyses were performed for the total mesophilic aerobic count, total mesophilic anaerobic count, total aerobic psychrotrophic count, proteolytic bacterial count, histamine, putrescine and cadaverine producer count. Proximate content on 0 and 12th day of storage, color changes of cephalothoraxes, pH and total volatile base nitrogen (TVBN) was the biochemical analysis performed. For the antimicrobial activity of various extraction solvent of musk lime, key lime and lemon, ethanol extracts exhibited remarkable diameter of inhibition zone (DIZ) compared to water and juice extract towards all of the tested microorganisms. Largest DIZ were obtained using ethanol extract of musk lime (39.7 mm), key lime (26.7 mm) and lemon (32.0 mm) particularly against Aeromonas veronii at 100% concentration level. As for juice extract, KL juice extracts revealed prominent antimicrobial activity compared to musk lime and lemon juice extracts. Accordingly, white shrimps treated with KL juice extract (100% concentration level) in combination with VP exhibited significant (p<0.05) lower count for all of the microbiological analysis performed. As for the total aerobic mesophilic count, significant (p<0.05) lower counts obtained in VP+KL, VP and SB+KL samples. Prominent total proteolytic counts were obtained from the 9th day of storage onwards in VP+KL and SB+KL samples. Similarly putrescine and cadaverine former counts were significantly lower in VP+KL and SB+KL samples. On the whole, VP+KL treated samples revealed a lowest bacterial count in the range of 4.37 to 4.91 log cfu/ g at 12 day of storage. As for proximate content, VP+KL samples retained highest percentage of protein on the 12th day of storage. Moreover, VP+KL and VP samples showed significant (p<0.05) results for the color changes of cephalothoraxes starts from the 6th day of storage. Besides, significantly lower TVBN content was obtained in VP+KL (5.33 mg N/ 100g) followed by VP (6.03 mg N/ 100g) samples on the 12th day of storage. Therefore, VP+KL treatment might be used as an alternative preservative method for post mortem storage of white shrimp and may recommend for quality preservation of other fishery products. The remarkable inhibitory activity of musk lime, key lime and lemon extracts of various extraction solvents (ethanol, water and juice) may attribute them as potential antimicrobial agents and natural preservatives as well.